Therapeutic potential of thymoquinone gel in stage II grade A periodontitis: a prospective clinical and biochemical evaluation - Nivedha Nedumaran; Arvina Rajasekar (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Periodontitis is a chronic inflammatory oral disease influenced by microbial plaque and oxidative stress, affecting human health and wellbeing. Conventional therapy with scaling and root planing (SRP) may benefit from adjunctive medicine with antioxidant and anti-inflammatory properties. Thymoquinone, derived from Nigella sativa, has shown promise in modulating oxidative stress and inflammation. However, there is limited clinical evidence regarding its adjunctive use in non-surgical periodontal therapy. Purpose: This clinical study aimed to evaluate the efficacy of 0.2% thymoquinone gel as an adjunct to SRP in treating stage II grade A periodontitis. Methods: Thirty patients diagnosed with stage II grade A periodontitis were randomly divided into two groups: Group 1 (Control), receiving SRP alone (n = 15), and Group 2 (Test), receiving SRP with 0.2% thymoquinone gel (n = 15). Clinical parameters, including the gingival index (GI), plaque index (PI), clinical attachment level (CAL), and probing pocket depth (PPD), were assessed. Additionally, oxidative stress index (OSI), total antioxidant capacity (TAOC), and total oxidant status (TOS) were measured in unstimulated saliva samples. Evaluations were conducted at baseline and three months post-treatment. Statistical analyses were employed to compare outcomes within and between groups. Results: Both groups demonstrated significant intragroup improvements (p < 0.05) in TOS, TAOC, CAL, PPD, GI, PI, and OSI from baseline to three months. However, intergroup comparisons revealed that Group 2 showed significantly greater improvement (p < 0.05) in all parameters except PI, which remained statistically insignificant (p > 0.05). Conclusion: The adjunctive use of 0.2% thymoquinone gel with SRP resulted in significantly greater improvements in clinical parameters (PPD, CAL, GI) and salivary oxidative stress markers (TOS, OSI, TAOC) compared with SRP alone. The study supports the potential role of thymoquinone as an adjunctive antioxidant agent in improving nonsurgical management of stage II grade A periodontitis.